Development of gluten-free rice bread: Pickering stabilization as a possible batter-swelling mechanism. (June 2017) - Yano, Hiroyuki; Fukui, Akiko; Kajiwara, Keiko; Kobayashi, Isao; Yoza, Koh-ichi; Satake, Akiyoshi; Villeneuve, Masumi
Abstract: In this study we sought to develop gluten-free rice bread without using additives. Breads with high specific volume, comparative to wheat bread, around 4 cm 3 /g, were obtained when rice flour with low starch damage (<5 g/100 g) was used as an ingredient. Microstructure analyses of the bubble wall in the fermenting batter revealed a "stone-wall" like structure resembling the microstructure of Pickering emulsion rather than that of typical wheat dough. Moreover, the surface tension of the dispersed solution of flour with low starch damage (4.7 g/100 g) was as low as 35 mN/m, while that of flour with high starch damage (9.8 g/100 g) was 47 mN/m. These data with the results of dynamic modulus measurements suggested a hypothetical mechanism in which Pickering stabilization facilitated swelling of the batter/bread. This paper proposes a possible example of Pickering foam/emulsion in food processing. Highlights: Rice flour with less starch damage makes bread without needing additives. Pickering stabilization facilitates swelling of the bread dough. Gluten-free rice bread as a new example of Pickering emulsion.